Islamic Education In Early 20th Century In China - Mai Jianjun (Yayasan Maslahatul Ummah Ilal Jannah, 2026)
This study examines the transformation of Islamic education among China's Hui Muslims during the early twentieth century, a period marked by profound political and cultural change. For centuries, the mosque-based Jingtang Jiaoyu (Scripture Hall Education) served as the cornerstone of Hui religious learning, preserving Islamic identity within a predominantly Han Chinese society. However, by the Republican era, this traditional system's limitations—particularly its avoidance of Chinese literacy, narrow vocational focus, and isolation from global Islamic scholarship—had become increasingly apparent. The fall of the Qing dynasty and the establishment of the Republic of China created new opportunities for educational reform. Constitutional guarantees of ethnic equality, the influence of the New Culture Movement, and the Hui community's growing political consciousness created conditions for reimagining Islamic education. Hui scholars and reformers responded by establishing modern Islamic schools that integrated Chinese language instruction and social sciences into religious curricula while maintaining Islamic identity. These reforms produced a new generation of leaders capable of navigating religious, social, and political spheres simultaneously. Through historical analysis and a case study of Chengda Normal School, this research demonstrates how these reforms successfully balanced tradition with modernization. The establishment of teacher training academies, the integration of secular subjects, and the reconnection with the wider Islamic world through study abroad programs enabled Hui Muslims to preserve their religious distinctiveness while engaging more fully with Chinese society and the global ummah. The Hui experience offers valuable insights into how minority religious communities negotiate cultural change without surrendering their core identity.